The engineer in the community joint ASCE/ICE conference, Bermuda, 1970. (Institution of Civil Engineers, 1971)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of joint ASCE/ICE conference held on Bermuda in 1970.